Morphological characteristics of models of generalized experimental periodontitis. Treatment with acisol - Y. V. Maskurova; T. V. Gayvoronskaya; N. V. Sokolovsky (Сеченовский вестник)
Recently, the alterative effect of stress on periodontium, which is associated with the disturbance of lipid peroxidation processes, is increasingly being considered. In this regard, in order to reduce the severity of clinical manifestations of periodontitis in the acute stage, it is advisable to use antioxidant and antihypoxic therapy. In an experimental study, a comparative analysis of inﬂammatory-destructive periodontal lesions was performed at different levels of stress, and the therapeutic effect of acyzole on the degree of regeneration of soft periodontal tissues under the given conditions was determined.